The - Hofmann, Helmut (Oxford University Press, 2008)
This book offers a comprehensive survey of basic elements of nuclear dynamics at low energies and discusses similarities to mesoscopic systems. It addresses systems with finite excitations of their internal degrees of freedom, so that their collective motion exhibits features typical for transport processes in small and isolated systems. The importance of quantum aspects is examined with respect to both the microscopic damping mechanism and the nature of the transport equations. The latter must account for the fact that the collective motion is self-sustained. This implies highly nonlinear couplings between internal and collective degrees of freedom --- different to assumptions made in treatments known in the literature. A critical discussion of the use of thermal concepts is presented. The book can be considered self-contained. It presents existing models, theories and theoretical tools, both from nuclear physics and other fields, which are relevant to an understanding of the observed physical phenomena